From winery waste to bioactive compounds and new polymeric biocomposites: A contribution to the circular economy concept - Ferri, Maura; Vannini, Micaela; Ehrnell, Maria; Eliasson, Lovisa; Xanthakis, Epameinondas; Monari, Stefania; Sisti, Laura; Marchese, Paola; Celli, Annamaria; Tassoni, Annalisa (My University, 2020)
The paper aims at optimising and validating possible routes toward the full valorisation of grape agrowaste to produce bioactive molecules and new materials. Starting from Merlot red pomace, phenol complex mixtures were successfully extracted by using two different approaches. Extracts obtained by solvent-based (SE) technique contained up to 46.9 gGAeq/kgDW of total phenols. Depending on the used solvent, the prevalence of compounds belonging to different phenol families was achieved. Pressurized liquid extraction (PLE) gave higher total phenol yields (up to 79 gGAeq/kgDW) but a lower range of extracted compounds. All liquid extracts exerted strong antioxidant properties. Moreover, both SE and PLE extraction solid residues were directly exploited (between 5 and 20% w/w) to prepare biocomposite materials by direct mixing via an eco-friendly approach with PHBV polymer. The final composites showed mechanical characteristics similar to PHVB matrix. The use of pomace residues in biocomposites could therefore bring both to the reduction of the cost of the final material, as a lower amount of costly PHBV is used. The present research demonstrated the full valorisation of grape pomace, an agrowaste produced every year in large amounts and having a significant environmental impact.
Keywords: Biocomposites; Biowaste; Grape pomace; Polyphenols; Pressurized liquid extraction; Solvent-based extraction